Algebra and Trigonometry 10th Edition

Published by Cengage Learning
ISBN 10: 9781337271172
ISBN 13: 978-1-33727-117-2

Chapter 2 - 2.7 - Inverse Functions - 2.7 Exercises - Page 229: 77


$f^{-1} (x)=x+3$ Domain of the function $f$ is: $[4, \infty)$. Domain of the inverse of function $f$ is: $[1,\infty)$.

Work Step by Step

We have $y=|x+4|+1=x-4+1=x-3$ To compute the inverse, we will have to interchange $x$ and $y$. $x=y-3$ Re-write as: $ y=x+3$ Replace $y$ with $f^{-1} (x)$. so, $f^{-1} (x)=x+3$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.